MICROPROPAGATION AND ELICITATION STUDIES IN ALOE VERA - Shukla, Nishita; Rao, Nagashree N; Sharma, Ashwani (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Micropropagation and elicitation studies of Aloe vera Methods: Standardisation of the regeneration protocol was done by using Murashige and Skoog (MS) media in combination with various plant growth regulators and elicitation studies were carried out by means of abiotic elicitors (salicylic acid, fructose and sodium chloride). Results: Direct regeneration through shoot tip gave the best response (0.2 mg/l Indole Butyric Acid (IBA) + 0.2mg/l 6-Benzylaminopurine (BAP)). Salicylic acid proved to be an effective abiotic elicitor, for suspension cultures of in vitro grown callus and also in vivo. It increased the content of polysaccharides, up to 7 times and phenolic compounds to almost 10 folds compared to untreated control kept under similar conditions. Conclusion: This study will make a path for the genetic transformation and metabolite enhancement along with their regulation, which can prove to be an asset towards pharmaceutical industry. Keywords: Aloe vera, Succulent plant, Micropropagation, Elicitation, Callus, Explant.